Information and Communication Technologies in Tourism 2022 2022
DOI: 10.1007/978-3-030-94751-4_36
|View full text |Cite
|
Sign up to set email alerts
|

Exploring “Planned Serendipity” and On-site Information Behavior on Smartphones

Abstract: The paper explores tourists’ smartphone-related information behavior on site in light of the concept of “planned serendipity”. The ability to gather information at anytime and anywhere can deeply influence tourists’ behavior, their information needs and the outcomes of their travel plans. In this study, the concept of planned serendipity is used to suggest that the outcome of travel information behavior on site is not entirely planned nor entirely serendipitous. The study employs the Experience Sampling Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Research on how tourists use smartphones to make onsite decisions remains in its infancy (Liu et al, 2022). Although recent studies (García-Milon et al, 2021;Kang et al, 2020;Liu et al, 2022;Mieli, 2022) have offered valuable insights into understanding decisions mediated by smartphones, these studies have not specifically focused on the onsite decisionmaking process. For example, Kang et al (2020) uncovered demographic differences in smartphone-based information search behavior as well as identifying differences in pre-trip and onsite information search behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on how tourists use smartphones to make onsite decisions remains in its infancy (Liu et al, 2022). Although recent studies (García-Milon et al, 2021;Kang et al, 2020;Liu et al, 2022;Mieli, 2022) have offered valuable insights into understanding decisions mediated by smartphones, these studies have not specifically focused on the onsite decisionmaking process. For example, Kang et al (2020) uncovered demographic differences in smartphone-based information search behavior as well as identifying differences in pre-trip and onsite information search behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Liu et al (2022) explored the decision contexts that trigger and support the use of smartphones in flexible travel planning in a destination. Finally, Mieli (2022) found that smartphones help tourists to find information that is location-specific and personalized, allowing for an optimized and flexible information search. However, few studies have explored how tourists use smartphones to achieve an optimal solution (the best possible decision) in onsite decision making.…”
Section: Introductionmentioning
confidence: 99%